하이브리드 코팅시스템에 의해 제조된 Mo-Si-N 박막의 미세구조 및 기계적 특성연구 - 허수정(Su Jeong Heo); 윤지환(Ji Hwan Yun); 강명창(Myung Chang Kang); 김광호(Kwang Ho Kim) (Biuletyn Uniejowski, 2006)
In this work, comparative studies on microstructure and mechanical properties between $Mo_2N$ and Mo-Si-N coatings were conducted. Ternary Mo-Si-N coatings were deposited on AISI D2 steel substrates by a hybrid method, where AIP technique was combined with a magnetron sputtering technique. Instrumental analyses of XRD, HRTEM, and XPS revealed that the Mo-Si-N coatings must be a composite consisting of fine $Mo_2N$ crystallites and amorphous $Si_3N_4$. The hardness value of Mo-Si-N coatings significantly increased from 22 GPa of $Mo_2N$ coatings to about 37 GPa with Si content of 10 at.% due to the refinement of $Mo_2N$ crystallites and the composite microstructure characteristics. The average friction coefficient of the Mo-Si-N coatings gradually decreased from 0.65 to 0.4 with increasing Si content up to 15 at.%. The effects of Si content on microstructure and mechanical properties of Mo-N coatings were systematically investigated.